Study of Contract Change Order (CCO) on Implementation Time in Building Construction Project - Tutang Muhtar Kamaludin; Andi Rusdin; Nirmalawati Nirmalawati (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
The aim of this research is to identify the main causes and effects of CCO in the construction of the Palu State Islamic University (IAIN) campus II building project for the Faculty of Tarbiyah and Teacher Training and the Faculty of Sharia and Islamic Economics Lecture Building. Tasks included conducting a field survey via a questionnaire and interviews with main parties; project owner, contractors and consultants who are directly related to the project. It was determined that the top three causes of CCO from project owner, contractor and consultant. The contractor has do CCO at the beginning of the project of 70% respondent, while consultant has changed contract order at mid-project implementation of 50% respondents and 70% at the end project implementation from the contractor. The results that are quite important from this study are the discovery of volume estimation errors and changes in work methods. Errors in estimating volumes are caused by the planning consultant's inaccuracy in planning so that there is a significant difference in volume from the initial contract with conditions in the field so that some work items experience an increase or decrease in volume